Ukraine : Fifth and Sixth Review under the Extended Arrangement; Staff Report; Staff Supplement and News Brief on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Ukraine's economic performance has been impressive with strong growth and declining inflation under the Extended Fund Facility (EFF). Executive Directors appreciated the macroeconomic performance, and emphasized that continued prudent monetary policies in combination with exchange rate flexibility will be essential to maintain low inflation. They urged the need for accelerating structural reforms, liberalizing the agriculture sector, restructuring the bank, and strengthening the transparency and governance in the energy sector. They agreed that the country has completed the fifth and sixth reviews under the EFF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet